Development of a compact test board for silicon sensors IV/CV characterization. (3rd December 2021) - Allard, Y.; De Lentdecker, G.; Hohov, D.; Robert, F.; Safa, A.; Vanlaer, P.
Abstract: To build silicon trackers of modern and future high-luminosity collider experiments, thousands of silicon strip modules have to be produced and tested. The modules in new trackers must reliably work usually during 5–10 years or more under harsh irradiation conditions, as it will be impossible to replace a failing module once installed inside the detector. It means that reliable and rigorous testing of strip modules and its components is mandatory. To sustain the production throughput we should be able to test several modules in parallel. For this reason a fast, reliable, scalable and cost effective production QC test bench has to be designed and implemented. For the CV and IV measurements of sensors and modules we are developing a low-cost (less than 500 €) integrated electronic board which will be scaled up to ten channels to measure DUTs in parallel. In the current work the design of the IV / CV board and the calibration procedure to increase the accuracy of the current and capacitance measurements, for which a special calibration dipole board based on tight tolerance capacitors and resistors has been designed, as well as future development plans are described.